Estimating the Returns to College Quality with Multiple Proxies for Quality - Black, Dan A.; Smith, Jeffrey A. (Journal of Labor Economics, 2006)
Existing studies of the effects of college quality on wages typically rely on a single proxy variable for college quality. This study questions the wisdom of using a single proxy given that it likely contains substantial measurement error. We consider four econometric approaches to the problem that involve the use of multiple proxies for college quality: factor analysis, instruments variables, a method recently proposed by Lubotsky and Wittenberg, and a GMM estimator. Our estimates suggest that the existing literature understates the wage effects of college quality and illustrate the value of using multiple proxies in this and other similar contexts.